Método Montessori para el refuerzo pedagógico matemático en estudiantes del quinto grado de la Unidad Educativa Orianga, Paltas 2024 - Sarmiento Calva, Juan Daniel (2024)
The focus of this paper is on the need to apply a method that enables students to improve their skills and understanding of concepts in the mathematics field, which will not only help them in daily life situations, but will also offer teachers the possibility to enhance their professional practice by performing alternative activities that are attractive to students. To this end, this paper’s main goal is to analyse the impact of the Montessori method on student mathematics teaching reinforcement. We selected as sample population the fifth-grade students from the Unidad Educativa Orianga school, it was a non-probabilistic sample for convenience composed of 19 students and one teacher. This research was of a mixed approach, descriptive-explanatory with a quasi-experimental design; We used the teacher’s interview technique and the evaluation for the students; also, the pre- and post-evaluation instruments were used for data collection. The results evidence that 58% of the students managed to master the required learning, 21% achieve the required learning, 5% are close to achieving the required learning, and finally 16% do not reach the required learning. Therefore, it is concluded that students present difficulties in learning mathematics such as logical reasoning, writing quantities, identifying numerical value and identifying quantities; consequently, a pedagogical plan was proposed called: "Reinforce, to improve my knowledge" which aims to provide students with an opportunity to improve their knowledge through the Montessori method activities in pedagogical reinforcement.